The effects of tumour necrosis factor-alpha and interleukin1 on an in vitro model of thyroid-associated ophthalmopathy; contrasting effects on adipogenesis. - O'FARRELLY, CLIONA (My University, 2006)
OBJECTIVE: Cytokines are likely to play a key pathogenic role in thyroid-associated ophthalmopathy (TAO). Anti-cytokine therapy has been proposed to be a possible treatment for active TAO. We aimed to establish the effects of selected cytokines on intercellular adhesion molecule 1 (ICAM1) expression, glycosaminoglycan (GAG) production and adipogenesis in orbital fibroblasts (OFs) from patients with TAO. METHODS: Orbital tissue was taken during surgery from eight patients with TAO and five control subjects. OFs were cultured and ICAM1 expression measured by flow cytometry. GAG production was measured by hyaluronic acid ELISA. OFs were grown in adipogenic media and the degree of adipogenesis quantified. RESULTS: Responses were similar in OFs from patients with and without TAO. Tumour necrosis factor-alpha (TNFalpha) and interleukin1 (IL1) (0.1 ng/ml) stimulated ICAM1 expression by eight- to ten-fold. Anti-cytokine agents inhibited the cytokine-upregulated ICAM1 expression by 90-99% (P<0.01). TNFalpha and IL1 (0.1 ng/ml) increased hyaluronic acid production by 44 and 95% (P<0.01) respectively. Anti-cytokine agents inhibited these responses by 79-138% (P<0.04).0.013 AU and -1.0; P<0.03) whilst IL1 (0.1 ng/ml) stimulated adipogenesis (+0.05 AU and +5.7; P<0.02) measured by oil-red-O extraction and visual assessment respectively. The anti-IL1 agent inhibited IL1-mediated adipogenesis by 69-106% (P<0.04). CONCLUSION: TNFalpha and IL1 stimulate ICAM1 expression and GAG production, but have opposite effects on adipogenesis in OFs in vitro. IL1 promotes adipogenesis and its effects can be blocked by anti-IL1 agents in vitro. These agents may be the anti-cytokine treatment of choice for clinical trials in active TAO
PUBLISHED
Keywords: Cytokines; Cytokines; Immunology, Inflammation & Infection